Edward R. Murrow pictured with academics (Muhlenberg President Levering Tyson is standing immediately right of Murrow) and honorary degree recipients at Muhlenberg College. (Tufts Archival Research Center, 2005)
8x10. On back: Muhlenberg College Convocation